2006
DOI: 10.1007/s00429-005-0076-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study of glycine receptors in the retina of the frog Xenopus laevis

Abstract: The expression of glycine receptors in the retina of clawed frog, Xenopus laevis was studied immunocytochemically. Glycine receptors (GlyRs), as revealed by means of several different antibodies, were mainly distributed in the inner (IPL) and the outer plexiform layers. Their composition was determined to include alpha2 and alpha3 subunits. Typical punctate appearance and specific lamination in the IPL were seen with each of the antibodies directed against the different GlyRs' subunits. A notion for diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Some scattered puncta are also observed in the INL. Similar patterns are seen with GlyRα3 immunostaining in the IPL, although scattered puncta are also detected in the OPL (Vitanova, 2006). …”
Section: Developmental Expression Patterns Of Glycinergic Phenotype Msupporting
confidence: 65%
“…Some scattered puncta are also observed in the INL. Similar patterns are seen with GlyRα3 immunostaining in the IPL, although scattered puncta are also detected in the OPL (Vitanova, 2006). …”
Section: Developmental Expression Patterns Of Glycinergic Phenotype Msupporting
confidence: 65%
“…1B) shows that each band is composed of great number of immunoreactive puncta. In our previous studies, we demonstrated similar punctate pattern of immunoreactivity for glutamate receptors in frog retina (Vitanova, 2006a), as well as for other types of membrane receptors, glycine and GABA, in frog and turtle retina (Vitanova, 2006b;Vitanova et al, 2001Vitanova et al, , 2004. The immunofluorescence caused by an antiserum that recognizes both GluR2 and GluR3 subunits is represented in Fig.…”
Section: Ampa Receptorsmentioning
confidence: 67%
“…Glycine is an important inhibitory neurotransmitter in the nervous system of vertebrates, where it has been investigated in various species [ 35 , 65 , 66 , 67 , 68 , 69 ]. Conversely, our understanding of glycinergic neurotransmission in invertebrates is much more limited ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%